Analysis of Infrastructure and Human Resources Readiness in the Transition of Outpatient EMR at Sartika Asih Hospital - Sali Setiatin; Pradesna, Syakira Ratu (Greenation Publisher & Yayasan Global Research National, 2025)
The transition from manual filing to Electronic Medical Records (EMR) is a strategic step to improve the efficiency and effectiveness of healthcare services. This study aims to analyze the readiness of infrastructure and human resources (HR) in supporting the transition to the EMR system at the Outpatient Department of Bhayangkara Hospital Level II Sartika Asih Bandung. A descriptive qualitative method was used, with data collected through field observations, interviews, and open-ended questionnaires. The results show that the infrastructure, including hardware and information systems, is already available and functioning in each service unit. However, technical issues such as unstable internet connectivity at certain times were still reported. In terms of HR, most healthcare personnel have understood how to use the EMR system through formal training, peer guidance, and direct work experience. The adaptation process has gone relatively well, although there are still differences in comfort levels and technical understanding among healthcare workers. These findings indicate that the overall readiness of infrastructure and HR is at a fairly good level. However, improvements in network quality and equitable distribution of training are still needed to support the successful, comprehensive, and sustainable implementation of the EMR system.